Songs of the Dead - McFetridge, Alan (2022)
Songs of the Dead is a photographic exploration of the aftermath of a devastating fire that impacted the community of Fort McMurray in Alberta Canada on the 3rd of May 2016. Six months after the fire, stimulated by media coverage and reflecting on the discourse surrounding dispossession and the environment, the project commenced at ground level with support of a Royal Photographic Society Environmental Awareness Bursary in a region inhabited by Anishinaabe1 located within Treaty 8 Territory, the traditional lands of the Cree, Dene and unceded territory of the Métis. The visual essay presented here is centred in the wake of a major fire event, however, it is also about human law and ecosystems. By traversing discussions on ethics within documentary photography and briefly exploring the history Aftermath of this medium, we argue how photography can better address socio-ecological issues within climate change through poetics. We offer a way of resisting the norms of documentary photography, resulting from subject and process-driven methods. Cover image: The Last Man - photo by Alan McFetridge